The Effect of Giving Emprit Ginger Boiled Water on Reducing Menstrual Pain in Adolescent Girls Aged 15-18 Years - Vidia, Henny; Sari, Surya Mustika (Jurnal MIDPRO, 2023)
ABSTRACTMenstrual pain is discomfort in the lower abdomen during menstruation caused by uterine spasms that can interfere with activity and require treatment. Emprit ginger boiled water is one of the non-pharmacological therapies that can be used to reduce menstrual pain. Naturally, emprit ginger is believed to contain oleoresin consisting of gingerol and shogaol which can function as an analgesic. The purpose of this study was to determine the effect of giving emprit ginger boiled water on reducing menstrual pain in adolescent girls in Gayaman Village, Mojoanyar Mojokerto. This type of research is an experimental quasy with a one group pre test-post test design approach. The population is adolescent girls aged 15-18 years who experience menstrual pain as many as 82 respondents. The sample size in this study was 68 respondents. Sampling is carried out using accidental sampling techniques. The instrument used in this study was a pain scale observation sheet. The results of the analysis were obtained before being given emprit ginger boiled water, half of the respondents experienced menstrual pain with a moderate pain scale of 34 (50%). After being given emprit ginger boiled water, most respondents experienced menstrual pain with a mild pain scale of 49 (72.1%). The results of the t-test test are obtained Ï = 0.00 â‰¤ Î± = 0.05 then H0 is rejected and H1 is accepted. This means that there is an effect of giving emprit ginger boiled water on reducing menstrual pain in adolescent girls aged 15-18 years in Gayaman Village, Mojoanyar District, Mojokerto. The results of this study can prove that emprit ginger boiled water given to adolescent girls who experience menstrual pain can help reduce menstrual pain. So emprit ginger boiled water can be used to reduce menstrual pain.